Perubahan Dimensi dan Warna pada Resin Komposit Nanofiller dan Microhybrid Akibat Pemanasan Suhu Tinggi Sebagai Referensi Identifikasi Forensik - Rachel Marcelia Hamada; Dwi Kartika Apriyono; Erawati Wulandari (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Backgrounds: Restorative dental material is one of the forensic experts directory assistance to determining the identity of the unknown victim who in burn condition. Determining the identity can be done through changes dimensions. Changes dimensions can be look of reduced weight and discoloration on the restorationat high temperatures. Composite resin restorations is one materials that is mostly used because it has mechanical characteristic, aesthetic and physical well compared to other restorative materials.Objective: To identify the changes ofdimensions such as the weight reduction and the changes ofcolor between nanofiller composite resin with microhybrid composite resin which is heated at high temperatures. Method and Material: The material used is nanofiller composite resin andmicrohybrid composite resin. The stageof thetreatment is done by heating the composite resin at three temperatures: 319oC, 412oC, 800oC then look at the changes ofcolor and the weight reduction.Results and Conclusion: The results of two way ANOVA test and Post Hoc LSD test showed a significant differences with p <0.05. Theconclusion is there are physical changes such as discoloration and weight reductionof the composite resin which is heated at high temperatures.Keywords: Nanofiler composite resin,Microhybrid composite resin,and heated at high temperature.